Cypriot High Schools as Cultural Mosaics: Students’ Perspectives and Experiences - Nicolaou, Anna; Nitsiou, Chrisa; Charalambous, Sophia (My University, 2007)
In recent years, world events have sent numerous groups of people searching for relocation opportunities around the globe. Consequently, communities that regarded themselves as homogeneous have found themselves faced with the challenges posed by cultural diversity and group heterogeneity. In the case of Cyprus, the establishment of new cultural and ethnic communities of people, coupled with the accession of the island to the European Union, have brought about dramatic changes to the demographic character of the island which have affected different aspects of society, including education. However, the state educational system has found itself unprepared to accommodate for the needs of its diverse student body so as to capitalize on the merits of multiculturalism and teach the students to view pluralism as an asset and equip them with the tools necessary to survive and prosper in a culturally diverse environment. Therefore, the need to adapt the educational system so as to teach students to see the diversity amongst them and in the society in which they live as an empowering and enriching element of their education has become imperative. This paper focuses on what data analysis revealed regarding student attitudes and experiences of cultural diversity in their school environments. Data were collected through questionnaires which were distributed to students of public secondary schools island-wide. This study is part of a larger two-year project funded by the Research Promotion Foundation in Cyprus which aimed at examining attitudes towards intercultural education and developing multicultural awareness in public schools.
Keywords: Cultural Diversity; Students’ Attitudes; Teachers’ Attitudes